The Effect of Scientific Approach in Teaching Reading Comprehension at the Twelfth Grade Students in SMAN 1 Wawonii. - Siti Hijar; Zalili Sailan; Kamaluddin Kamaluddin (Journal of Language Education and Educational Technology (JLEET), 2020)
The purpose of study is to examine whether significant differences exist in students’ pre-test and post-test reading comprehension as a result of experiencing instruction using scientific approach, to examine whether significant differences in students’ test scores exist between those attending scientific approach and those experiencing conventional instruction, and to elaborate how students perceive the scientific approach, particularly in reading comprehension at the twelfth students grade in SMAN 1 Wawonii. The data were obtained from students’ pre-test and post-test scores, SEEQ questionnaire, and open-ended questions. The finding revealed that significant differences exist in students’ pre-test and post-test reading comprehension as a result of experiencing instruction using scientific approach, p (.000) < 0.05. The finding also indicated that significant differences in students’ test scores exist between those attending scientific approach and those experiencing conventional instruction p (.000) < 0.05. Furthermore, the finding also showed that majority of students agreed that the scientific approach was effective to increase their reading comprehension. Keywords: Scientific approach; Reading comprehension; Teaching approach; Effectiveness